Assessment of nutritional status, physical fitness and physical activity of school going adolescents (12-15 years) in Delhi - Shanza Ferozi; Anu Gupta Taneja; Neha Bakshi (BMC, 2024)
Abstract Background Adolescence is a distinct period that is crucial for setting the foundation for long-term health. Objective To assess the nutritional status, physical fitness, and physical activity of adolescents. Methods The present cross-sectional study recruited 100 adolescents purposively. Information regarding general profile and lifestyle-related factors was collected using a questionnaire. Anthropometric data such as height, weight, BMI, and body fat% were collected using appropriate equipment. Physical fitness was assessed using a battery adapted from FITNESSGRAM® and PAQ-A assessed the physical activity. Dietary intake was analysed using a 2-day 24-hour dietary recall. Result The study revealed, 19% of the participants were overweight and 6% were obese. The majority (74%) were physically inactive and 15% had high body fat %. There was lower consumption of energy, carbohydrates, iron, and calcium, than the recommendations. Also, physical activity scores were negatively associated with macronutrient intake and trunk lift (strength and flexibility) [p < 0.05]. Data showed lower physical fitness scores. BMI and hand-grip strength was positively correlated [p < 0.05]. Push Ups (endurance) and Standing Broad Jump (power) showed a negative correlation with body fat%. Tennis ball throw and PACER (cardiorespiratory fitness) were positively associated with protein intake. A multiple regression analysis significantly showed that a unit increase in cell phone usage increases body fat% by 11.64 units. Standing broad jump increases by 38.6 cm and decreases with 28.76 cm with a unit increase in playing outside and tuitions timings respectively. Conclusion Poor nutritional status, physical fitness, and physical activity were reported among adolescents. It is imperative to plan intervention strategies to improve the overall health of adolescents.